Argonaute-crosslinking and immunoprecipitation deciphers the liver miR-122 targetome - Navarro, Alfons (Non-coding RNA Investigation, 2017)
The profiling of microRNA (miRNA) expression in the liver by different groups has revealed that miR-122 is one of the most abundant miRNAs in this organ, accounting for 70% of miRNA expression in the liver (1-4). A systematic study of the miRNA patterns of different tissues in mice also demonstrated that miR-122 was a tissue-specific miRNA, highly enriched in liver tissue but absent from other tissues (5). The miR-122 sequence is completely conserved in vertebrates and no orthologues have been detected either in D. melanogaster or in C. elegans, indicating that miR-122 is probably linked to the appearance of the liver in vertebrates (6). In this line, the described functions of miR-122 are closely related to the regulation of specific hepatic processes, including cholesterol and lipid metabolism (7,8). Interestingly, miR-122 has been demonstrated to play a role in the regulation of hepatic polyploidy (9), a defining feature of the liver, and is crucial for hepatitis C virus replication in the liver (10). During carcinogenesis, miR-122 becomes downregulated and its expression levels are indicative of patient outcome in hepatocellular carcinoma (HCC) (11). Moreover, two miR-122 Knockout (KO) mice models, germline KO and liver KO, showed that inhibition of miR-122 activated an inflammatory process in the liver that led to hepatitis in the short term and to HCC in the long term (12). In contrast, the delivery of miR-122 to a MYC-driven mouse model of HCC strongly inhibited tumorigenesis, reinforcing the role of miR-122 as a tumor suppressor gene (12). Although several targets associated with previously described functions of miR-122 have been identified, the miR-122 targetome in normal liver and in HCC remained incomplete until now.